Chiral recognition in a single molecule: a study of homo and heterochiral butan-2,3-diol by Fourier transform microwave spectroscopy - Paul, J; Hearn, I; Howard, B (2007)
The microwave Fourier transform spectrum of butan-2,3-ol has been recorded in the range 5-18 GHz. The molecule possesses two chiral centres and exists in two distinct forms, one of which is homochiral ((R,R) or (S,S)) and is overall chiral, and the other which is heterochiral ((R,S) or (S,R)) and is overall meso. Detailed ab initio calculations enabled investigation of the relative stability of the many conformations exhibited by each form of the molecule. It is shown that the lowest energy forms in each case possess an internal hydrogen bond. The spectrum of the heterochiral (meso) form could be readily identified and analysed. The homochiral form, however, exhibits a tunnelling motion of about 1 GHz, in which the hydrogen bonded OH groups interchange their roles. Deuteration of one of these OH protons quenches the tunnelling motion, aiding the assignment of the spectrum. In all cases, deuteration of the hydroxyl groups was used to locate the positions of the OH hydrogen atoms and helped to confirm the identification of the conformers present.